Outer membrane vesicles from Escherichia coli as a presentation platform for AR-23 antiviral peptide - Mensitieri, Francesca; Dell’Annunziata, Federica; Gaudino, Giulia; Folliero, Veronica; Franci, Gianluigi; Dal Piaz, Fabrizio; Izzo, Viviana (Frontiers in Molecular Biosciences, 2025)
IntroductionAnti-microbial peptides (AMPs) are a well-established alternative among antiviral and antibacterial agents, having considerable advantages over traditional antimicrobials in terms of biocompatibility and limited resistance development. However, a general poor bioavailability and short half-life limit their large-scale implementation. In this framework, different strategies are being explored, such as AMPs encapsulation or their functionalization on antigen-presenting platforms. In this work the evaluation of Escherichia coli (E. coli) derived Outer Membrane Vesicles (OMVs) as antiviral presenting platforms is described.MethodsOMVs were engineered through the recombinant overexpression of an outer membrane chimeric protein, ClyA-AR23, obtained by combining Cytolysin A (ClyA) with the AR-23 antiviral peptide, derived from frog skin and active against herpes simplex viruses. LC-MS/MS was used to screen the presence of the recombinant protein in cells and OMVs. Plaque reduction assay after pre-incubation treatment and qPCR on viral transcript were used to evaluate ClyA-AR23 OMVs antiviral activity of the engineered vesicles.ResultsThe expression of ClyA-AR23 protein was verified in recombinant E. coli cells and OMVs and the surface exposure of ClyA C-terminus was confirmed. Engineered ClyA-AR23 OMVs negligible cytotoxicity effect was assessed on VERO-76 cells. Both control and functionalized OMVs were used in pre-incubation treatment with HSV-1, HSV-2, SARS-COV2 and PV-1. Results highlighted that ClyA-AR23 OMVs did effectively impair HSV-1 and HSV-2 replication cycle in a dose dependent manner.DiscussionIn this work we provided a first evidence of AMPs functionalization on membrane vesicles of bacterial origin. The systems demonstrated to be active towards HSV-1 and HSV-2 viruses with negligible cytotoxicity on VERO-76 cells.